WOMEN AND PEACE PROCESSES IN NIGERIA - EMMANUEL ACHUS JAH; AMINA NKANDAK KURMI; TANKO SHAWULU PAUL; LONGPOE HENTUANG HENRY (International Studies Journal, 2022)
The position of women in peace process is of significance in brokering sustainable peace in the society. With them being the most affected next to the children in any violent conflict situation, they are wont with the wherewithal to approach peacebuilding with their care giving disposition. But they are denied this privilege owing to their gender status as customs and power relation in the society prescribe. The Agency Theory is used to expound this study. This inquest relies on secondary data,therefore content analysis is used to make end inferences. It recommends that women should not be seen as second fiddle and peaceful while men dominant and violent, there should be cultural reorientation in Nigeria where obnoxious practices of relegation of women to the background be prohibited and the democratic space in Nigeria should presentvents for the implementation of greater gender equality and offer a window for change. It however concludes that women hold in trust all ascribed status in the society and perform assigned functions with utmost good faith which endear their having positive outcome in such. Peace process can best be delivered by not only the men but women inclusive.